Knowledge on maternal and young child nutrition of service providers and functionality of nutrition committees in selected areas in the Philippines - Gordoncillo, Normahita P.; Talavera, Ma. Theresa M.; Paunlagui, Merlyne M.; Gordoncillo, Prudenciano U.; Barba, Corazon VC.; Bustos, Angelina R.; Africa, Leila S.; Carada, Wilfredo B.; Torres, Zenaida R. (2017)
Background: The Philippines continues to face the problem of double burden of malnutrition. Local nutrition committees have been formed to address maternal and child malnutrition. The committees is composed of various stakeholders whose awareness and knowledge of nutrition concepts are varied. Likewise, the functionality of the local nutrition committees is varied. It is important to know the level of awareness and knowledge of the service providers as this affects the functionality of the local nutrition committees in delivering nutrition services.
Objective: This study aimed to examine the awareness and knowledge of service providers on selected nutrition concepts and the functionality of local nutrition committees in selected areas in the Philippines.
Methodology: A cross-sectional study was done with members of the local nutrition committees, such as the Municipal Nutrition Action Officer and Municipal Health Officer as respondents. Data collection instruments were developed. Data were analyzed using descriptive analysis and Tobit regression model.
Results: The total knowledge and functionality scores were low and varied across regions. This is indicative of considerable possibilities for improvement in terms of the appropriate knowledge and good practices in health and nutrition interventions. These is a significant differences between the level of knowledge and of functionality and data tend to suggest that knowledge does not necessarily translate to good practices in food and nutrition security services. Furthermore, the analysis showed that awareness of certain reference terms does not necessarily lead to a meaningful conceptual understanding of its dimensions, e.g. nature, basis, or mechanisms.
Conclusion: The level of knowledge that influences institutions and service providers' level of functionality merits serious considerations in terms of capability building needs. There is a need for a full comprehension of commonly used concepts and terms in nutrition at the local level since total or partial lack of understanding will not translate to practice. The variability in the level of knowledge and functionality can serve as the basis for prioritization.
Keywords: Nutrition; Nutrition assessment